1990
DOI: 10.1128/aem.56.6.1806-1812.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of 14 C-Ring-Labeled Synthetic Lignin Correlates with the Production of Lignin Peroxidase, not of Manganese Peroxidase or Laccase

Abstract: Recently, Mn(II) has been shown to induce manganese peroxidases (MnPs) and repress lignin peroxidases (LiPs) in defined liquid cultures of several white rot organisms. The present work shows that laccase is also regulated by Mn(II). We therefore used Mn(II) to regulate production of LiP, MnP, and laccase activities while determining the effects of Mn(II) on mineralization of ring-labeled synthetic lignin. At a low Mn(II) level, Phanerochaete chrysosporium and Phlebia brevispora produced relatively high titers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(51 citation statements)
references
References 37 publications
(38 reference statements)
6
43
1
1
Order By: Relevance
“…These data not only indicated for the first time that the LiPs play a dominant role in lignin degradation but also showed that a strain of P. chrysosporium which lacked LiP activity could still degrade lignin, albeit to a minor extent. These conclusions were independently corroborated by later studies of Bonnarme and Jeffries [39] and Perez and Jeffries [45], who observed that LiP production is completely suppressed in the presence of high levels of Mn(II) and that only 10-11% of the lignin degradation occurs in such a medium, as compared to an identical medium with low levels of Mn(II) in which both LiPs and MnPs are produced. The above results further indicated that LiP production in P. chrysosporium is regulated differently, at least in some aspects, from MnP production and that LiPs play a dominant role in mineralizing synthetic [14C]lignin in liquid cultures.…”
Section: Regulation Of Lip Productionsupporting
confidence: 60%
“…These data not only indicated for the first time that the LiPs play a dominant role in lignin degradation but also showed that a strain of P. chrysosporium which lacked LiP activity could still degrade lignin, albeit to a minor extent. These conclusions were independently corroborated by later studies of Bonnarme and Jeffries [39] and Perez and Jeffries [45], who observed that LiP production is completely suppressed in the presence of high levels of Mn(II) and that only 10-11% of the lignin degradation occurs in such a medium, as compared to an identical medium with low levels of Mn(II) in which both LiPs and MnPs are produced. The above results further indicated that LiP production in P. chrysosporium is regulated differently, at least in some aspects, from MnP production and that LiPs play a dominant role in mineralizing synthetic [14C]lignin in liquid cultures.…”
Section: Regulation Of Lip Productionsupporting
confidence: 60%
“…3E). In analogous chromatographic conditions in P. chrysosporium [15,20] and Bjerkandera spp. [17] cultures, LiP peaks exhibiting lower retention time than those showing MnP activity has been described.…”
Section: Resultsmentioning
confidence: 99%
“…Fast protein liquid chromatography (FPLC) of haemproteins was performed according to Perez and Je¡ries [15]. Peak detection was monitored at 280 nm (for total proteins) and at 405 nm (for haemproteins).…”
Section: Fplc Haemprotein Analysesmentioning
confidence: 99%
“…The production of LiP correlates, i.e. is simultaneous with the degradation of JaC-[Ring]-DHP to 14CO2 in P. radiata [28] and in P. chrysosporium [62]. Apparently, high evolution of 14CO, from 14C-[Ring]-labeIled DHP is in good correlation with the production of LiP in the cultures, provided that the fungus produces MnP.…”
Section: Degradation Of 14c-labelled Synthetic Lignin (Dhp) By Differmentioning
confidence: 96%